The Influence of Particle Size, Fluidization Velocity, and Fuel Type on Ash-Induced Agglomeration in Biomass Combustion - Gatternig, Bernhard; Karl, Jürgen (Frontiers in Energy Research, 2014)
Agglomeration of the bed material is one of the main obstacles for biomass utilization in fluidized bed combustors. Especially high-potential fuels such as fast growing energy crops or biogeneous residues are affected, due to their high content of alkaline metals. Despite ongoing research efforts, the knowledge base on what fuels are affected is still limited. This paper describes the design and installation of two lab-scale reactors for the experimental determination of agglomeration temperatures. The reactor concept and measurement method were developed under consideration of experiences from existing test rigs published in literature. Preliminary tests confirmed a reproducibility of ±5°C for both new reactors. The results of an extended measurement campaign (156 test runs of 25 fuel species at a wide range of the operational parameters “bed particle size”, “gas velocity”, “bed ash accumulation”), based on “design of experiment” criteria, showed high agglomeration tendencies for residues (e.g., dried distillery grains, corn cobs) while woody energy crops (e.g., willow, alder) exhibited very stable combustion behavior. The operating parameters influenced the agglomeration behavior to a lesser degree than different ash compositions of fuel species tested. An interpolation within the design of experiment factor space allowed for a subsequent comparison of our results with experiments reported in literature. Good agreement was reached for fuels of comparable ash composition considering the interpolation errors of ±32°C on average.